Risk factors for chronic disability in a cohort of patients with acute whiplash associated disorders seeking physiotherapy treatment for persisting symptoms - Williamson, E; Williams, MA; Gates, S; Lamb, SE (Elsevier, 2014)
Objectives: (1) To identify risk factors for chronic disability in people with acute whiplash associated disorders (WAD). (2) To estimate the impact of the numbers of risk factors present.